G332(P) Glucose transporter–1 deficiency syndrome (GLUT1DS): Survey of clinical presentation in the UK and Ireland. (7th April 2014) - Mehta, V; Gayatri, N; Hart, T
Abstract : Aim: To study the phenotype of GLUT1DS in the UK and Ireland. Method: A national surveillance study was performed in conjunction with the BPNSU over the 2 year period (February 2011 to February 2013) to investigate the phenotype of GLUT1DS. Patients were identified via routine BPNSU communication emails sent to all paediatric neurologists in the UK and Ireland. Questionnaires were sent to responding clinicians and anonymized phenotypic information was collected on clinical presentation, disease course and the results of diagnostic genetic investigations. Local research governance team confirmed that no ethical approval was required. Results: 78 new cases were notified over the 2 year period but only 27 completed questionnaires returned representing an overall response rate of 34.6%. 15 were boys and 12 were girls. 59% of them presented in first two years of life. Common clinical features were epilepsy in 22, movement disorder in 17, microcephaly in 11 and developmental delay in all of them in one or more domains. Absences were the commonest seizure type. Movement disorders included ataxia in 11, dystonia in 5 and exercise induced paroxysmal dystonia in 5. Fasting CSF glucose available in 20 cases was ≤2.3 and lactate available in 13 cases was ≤1.3. 24 cases tested had SLC2A1 mutations providing genetic confirmation. EEG showed generalised (14) and focal abnormalities (3). Imaging showed abnormalities only in 5. Of the 17 patients who received ketogenic diet (KD), epilepsy improved in 7 and movement disorder in 11. Genotype phenotype correlation could not be carried out due to small number of cases and the large range of mutations identified. Conclusion: Our findings are consistent with previous reports that majority of patients present with the phenotype of early onset epilepsy, developmental delay and/or complex movement disorder. A small proportion of patients did not have epilepsy. No case of isolated developmental delay due to GLUT1DS was reported. Genetic diagnosis was possible in majority. Those with isolated movement disorders showed consistent response to KD.